The forgotten girl - Brown, India Hill, 1991- (Scholastic Press, 2019)
Eleven-year-olds Iris and her best friend Daniel sneak outside to play in the woods behind their homes to experience the first snowfall. The pair discover the grave of a young girl named Avery who was their age when she died. Avery begins to haunt Iris in her dreams, so she and Daniel decide to research the grave for a school project, discovering it is a forgotten segregated African American cemetery. The pair make a plan to give the cemetery the proper respect and recognition it deserves in order to help Avery attain peace.